Expectant management for a high-risk pregnancy patient who had preterm premature rupture of membranes with placenta and vasa praevia plus velamintous cord insertion - Abdalla, Mena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Objective of the study was to share a case of high risk pregnancy with premature preterm rupture of membranes (PPROM), placenta and vasa praevia plus velamintous cord insertion. PPROM carries the risk of increasing rates of neonatal respiratory distress syndrome, neonatal brain prematurity, and electrolyte imbalance. Having placenta previa and vasa praevia carries a significant risk of recurrent bleeding and increases the risk of making the pregnancy threatened by the antepartum haemorrhage with the chance of losing the baby and subsequent morbidities and mortalities to the mother and the baby. The velamentous cord insertion is linked to decreased foetal growth and premature births. Herein, we present the case of 28 years old that had multiple risk factors during her pregnancy in the form of having multiple miscarriages, stillbirth, PPROM early at 20 weeks of her gestation, placenta praevia, vasa praevia and velamentous cord insertion. Moreover, despite the above risk factors, which made the pregnancy very high risk, by expectant and management plans, we could push her pregnancy to reach near maturity and deliver her baby safely without complications either to the mother or to her baby. It could be theoretically imagined that the placenta praevia worked as a sealed system or a valve and prevented more leakage of the liquor in this PPROM case. Besides that, we can consider that the cervical stitch she had at 14 weeks, had a role in narrowing the cervical canal and decreasing the diameter of the membrane that has ruptured.